Materials, forensics and feminist geopolitics. (October 2021) - Sharp, Jo
This article seeks to advance the case for feminist geopolitics that recognises the challenges both to the Enlightenment individual and the discursive turn in geography posed by 'new materialisms'. I will argue that for a distinctively feminist geopolitics a consideration of the way that representational categories align the material around bodies is vital. After a brief discussion of feminist geopolitical approaches, the article moves on to consider accounts of new materialism and assemblage approaches as they are applied to geopolitics, before moving on to consider what a forensic approach might offer to a materialist feminist geopolitics.